ANALISIS SUMBER DAN PENGGUNAAN DANA PADA KOPERASI SIMPAN PINJAM PKK â€œSEJAHTERAâ€ DIKECAMATAN MOOK MANAAR BULATN - -, Pradilawati - (EKONOMIA, 2017)
The research aim to analyze the source of funds in credit unions PKK Â â€Sejahteraâ€ in the districts of Mook Manaar Bulatn in 2012th , 2013th Â and 2015Â  has been used effectively.The theoretical basic of this research is financial management, definition of credit unions, and financial reports.The instrument of analysis is the ratio of balance sheet,the reports of transmutation of cooperative fund, the report of source and usage of fund, and the liquidity ratio, Leverage, and Activity.Â Â The results of the ratio balance sheet indicates that reduction of efficient assets, and capital, the assets is still not transmutation but sustainable to increase of debt. In the reports changes of capital showed a reduction in working capital and increase of current liabilities. While the reports of source and usage of work capital indicates that the source of funds credit unions PKK â€œSejahteraâ€ comes from the principal, compulsory savings, reserve capital and SHU of year while the use of work capital of credit union PKK â€œSejahteraâ€ for purchase of equipment cooperative. The liquidity ratio indicates the cash ratio improved and current ratio is not good. Total leverage ratio to equity and total debt to asset showed improved performance of cooperative. While the activity ratio of total asset turnover and working capital turn over has decreased. Sources of funds in the cooperative PKK â€œSejahteraâ€ has been used effectively who evidenced by the increase in work capital from 2014th to 2015th amounted to Rp. 21.808.630,88.the conclusion, funds in savings and credit cooperative cooperatives PKK â€œ Sejahteraâ€ has not been used effectively.